Effects of Disease-Worsening Following Withdrawal of Etanercept or Methotrexate on Patient-Reported Outcomes in Patients With Rheumatoid Arthritis: Results From the SEAM-RA Trial. Issue 1 (22nd January 2023) - Curtis, Jeffrey R.; Stolshek, Bradley; Emery, Paul; Haraoui, Boulos; Karis, Elaine; Kricorian, Greg; Collier, David H.; Yen, Priscilla K.; Bykerk, Vivian P.
Abstract : Background/Objective: The effect of treatment withdrawal on patient-reported outcomes (PROs) in patients with rheumatoid arthritis (RA) whose disease is in sustained remission has not been well described. This analysis aimed to compare PRO changes in patients with RA following medication withdrawal and disease worsening. Methods: SEAM-RA (Study of Etanercept and Methotrexate in Combination or as Monotherapy in Subjects With Rheumatoid Arthritis) was a phase 3, multicenter, randomized withdrawal, double-blind controlled study in patients with RA taking methotrexate plus etanercept and in remission (Simple Disease Activity Index ≤3.3). Patient's Global Assessment of Disease Activity, Patient's Assessment of Joint Pain, Health Assessment Questionnaire–Disability Index, and 36-Item Short-Form Health Survey were evaluated for 48 weeks following methotrexate or etanercept withdrawal. Treatment differences for patients with versus without disease worsening were evaluated using a 2-sample t test for continuous end points and log-rank test for time-to-event end points. Results: Of 253 patients, 121 experienced disease worsening and 132 did not. All PRO scores were similar to those of a general population at baseline and deteriorated over time across the study population. The PtGA and Patient's Assessment of Joint Pain values deteriorated less in those on etanercept monotherapy compared with methotrexate monotherapy. More patients with versus without disease worsening experienced deterioration that was greater than the minimal clinically important difference (MCID) for all PROs tested. In patients with disease worsening, PtGA deterioration more than the MCID preceded Simple Disease Activity Index disease worsening. Conclusions: Etanercept monotherapy showed benefit over methotrexate in maintaining PRO scores. Patients with disease worsening experienced a more rapid worsening of PtGA beyond the MCID versus patients without disease worsening. Categories: autoinflammatory disease, biological therapy, DMARDs, rheumatoid arthritis